The Bath conspiracy - Dams, Jeanne M. (Dams, Jeanne M. Dorothy Martin mysteries, 2021)
"Retired chief constable Alan Nesbit and his wife Dorothy Martin are in the beautiful historic city of Bath to celebrate Dorothy's birthday, enjoying the city's elegant surroundings, sightseeing, shopping - and champagne. But the celebrations are curtailed when they discover a curious assortment of loot in their car boot during a trip to Stonehenge - from precious artefacts to cheap jumble sale trinkets. The stolen items are linked to various historic sites in Bath, but how did they end up in the Martins' car? As Dorothy and Alan seek to prove their innocence and catch a thief, they are soon swept into a conspiracy that runs much deeper and darker . . ."--Publisher.